Request Strategies in Javanese and Balinese Speakers: A Cross-Cultural Pragmatic Study - Imamah, Fitria Habibatul; Haryono, Aura Hilda (Journal of Pragmatics Research, 2026)
This study utilizes qualitative descriptive research designs to analyze and compare the request strategies of Javanese and Balinese speakers based on cross-cultural pragmatic studies. The data were obtained using the Discourse Completion Task (DCT) method which was compiled based on two social variables Brown & Levinson (1987), called power and distance from 24 Javanese speakers and 24 Balinese speakers and analyzed using the Cross-Cultural Speech Act Realization Project (CCSARP) method from Blum-Kulka and Olshtain (1984), by classifying head acts in three strategies; 1) direct conventional, 2) indirect, and 3) nonconventional indirect. This study's results are generally dominated by direct conventional strategies, in which social variables, specifically power and distance, serve as the primary determinants in speech selection. While common patterns are observed in situations involving intimate relations or high-authority positions, such as interactions between friends, superiors and subordinates, or husbands and wives, significant disparities emerge in low-power contexts. Javanese speakers tend to employ conventional indirect strategies when interacting with lecturers, whereas Balinese speakers more frequently utilize such strategies in the context of children addressing parents. Culturally, the selection of these strategies is a manifestation of deeply rooted politeness values, specifically the concept of andhap ashor through the unggah-ungguh basa system (Krama/Ngoko) in Javanese society, and the principle of anggah-ungguhing basa Bali, which is influenced by social stratification (wangsa) and the Tri Hita Karana philosophy. Both aim to preserve social harmony and mutual respect within interpersonal interactions.